Scales Feature Foot Scanners as Parameters of Flat Feet in Children - Adelia Nadyalishandi Nugroho; Nadila Ekasiti Kamarukmi; Abdul Ghufron; Menik Dwi Kurniatie (Universitas Respati Yogyakarta, 2023)
The primary function of the legs is to provide the necessary support and encouragement for human bipedal movements. Flat feet or also known as pes planus, is a problem that is often encountered in daily pediatric practice for most children. This study aims to classify the shape of the soles of the feet in children aged 6-9 years to be divided into three parts, namely high arch, normal arch and flat arch. Clarke's angel is defined as the angle obtained by a tangent that joins the medial edge of the first metatarsal head and the heel, on the second line connects the metatarsal caput one with the centre of the longitudinal arch of the medial side. Of the 30 children, 66.67% (20 students) had a flatfoot foot shape and 33.33% (10 students) had a normal foot sole shape and none of the students had a cavus arch foot sole shape. The mode in children with normal legs is Enough with a percentage of 60% and in children with flatfoot is bad with a percentage of 75%. This proves the relationship between flatfoot and static balance in children. From the research we conducted, it can be concluded that the featured scales we made can capture the image of a child's feet to identify flat feet and the relationship between flat feet and the static balance of a child. From the research that has been carried out, we compare existing data using three methods. The primary method we use is Matlab software with comparison data using wet footprints and stork stand tests, which shows excellent accuracy and can be a reference for measuring the soles of the feet in the future.